Ancestry - O'Leary, Eileen (Eileen Kelly), 1946- (Book collections on Project MUSE., 2020)
"In this eclectic collection one theme remains overall: How does one live a good life? If you're Pat Graves you change your name to Cecile Collette, move to Cleveland and join three churches and the rotary. For Cecile, who will reinvent herself again before the story ends, it may be possible to make Michigan and everything else she touches beautiful, but she'll come to grief when she tries to redesign another human being. In the title story, Mackenzie, a girl without looks or potential, builds a full life in Paris on the sketchy belief that she had an ancestor renowned for being dauntless. College freshman Adam, holding a fantasy of his newly discovered father, finds the man broke and foolish, still he does all he can to rescue his dad from a disastrous contract. Kate, convinced she's doing the right thing, helps her cousin gain full custody of his daughter, only realizing years later the truth of what happened. Watching CNN, a grandmother recalls a date she once had with a man now giving advice on foreign policy. Whether set in Scandinavia, America, France, England, Australia or Nepal, these stories champion those who are tenacious in the face of life's surprises"--